Ethnoracial Variation in Women's Exposure to Intimate Partner Violence. (February 2016) - Clark, Hannah M.; Galano, Maria M.; Grogan-Kaylor, Andrew C.; Montalvo-Liendo, Nora; Graham-Bermann, Sandra A.
While intimate partner violence (IPV) has been acknowledged as a national public health concern, little research exists that directly assesses differential exposure to IPV for distinct ethnoracial groups. The current study compared the rate, severity, and type of IPV exposure across samples of White, African American, and Latina women ( N = 180). Participants reported rates of exposure to violence on measures of physical assault, psychological aggression, injury, and sexual coercion; each subscale contained items denoting both mild and severe levels of violence. Multiple regression analyses indicated that women's frequency of exposure to sexual coercion, and severe and injurious violence significantly differed based on participants' ethnoracial identification, such that Latina women experienced disproportionate levels of violence relative to White and African American peers. Mothers' monthly income, level of education, general health, and relationship status also emerged as significant predictors of violence exposure. Results support the development of culturally sensitive adaptations of IPV interventions, targeting not only Latina populations but also women who are single, low-income, and educationally underserved.